A solution-processable hybridized local and charge-transfer (HLCT) phenanthroimidazole as a deep-blue emitter for efficient solution-processed non-doped electroluminescence device. (November 2021) - Sudyoadsuk, Taweesak; Petdee, Sujinda; Chasing, Pongsakorn; Therdkatanyuphong, Pattarawadee; Kaiyasuan, Chokchai; Waengdongbung, Wijitra; Namuangruk, Supawadee; Promarak, Vinich
Abstract: Most highly efficient hybridized local and charge-transfer (HLCT)-based organic light‐emitting diodes (OLEDs) are multi-layer devices fabricated by thermal vacuum evaporation techniques, which are inappropriate for the simplified device fabrication process. However, there are only a couple of reported examples of solution-processed HLCT OLEDs, particularly deep-blue OLEDs. Herein, we design and synthesize a solution-processable HLCT emitter, CPPI, in which 1, 2-diphenyl-phenanthroimidazole (PI) as an acceptor core is substituted by three 3, 6-di- tert -butyl- N -phenyl-carbazole (CP) moieties as a donor and hole-transporting/solubilizing unit. The HLCT and photophysical properties are thoroughly examined by theoretical and experimental methods. CPPI exhibits HLCT characteristics with intense deep-blue color emission, high thermal and electrochemical stability, and decent hole-transporting ability. The molecule is successfully fabricated as a solution-processed non-doped emitter in organic light-emitting diodes (OLED). The solution-processed OLED retains efficient and stable deep-blue color emission (CIE coordinates of (0.157, 0.089)) with a narrow FWHM of 66 nm, an EQEmax of 3.39% and a high exciton utilization efficiency of 42.4%. Crucially, this result signifies an advance in developing a solution-processable HLCT molecule as an emitter for solution-processed non-doped OLEDs. Graphical abstract: New HLCT emitter, CPPI, comprising of 1, 2-diphenyl-phenanthroimidazole and 3, 6-di- tert -butyl- N -phenyl-carbazole achieves a solution-processed deep-blue non-doped OLED with CIE coordinates of (0.157, 0.089), an EQEmax of 3.39% and a exciton utilization efficiency of 42.4%. Image 1 Highlights: New solution-processable HLCT emitter (CPPI) exhibit intense deep-blue emission. CPPI was efficiently employed as a solution-processed non-doped emitter in OLED. Simple structured OLED attains high EL performance with CIE coordinates of (0.157, 0.089) and an EQEmax of 3.39%.